La investigacion de frijol en campos de agricultores de America Latina: memorias de un taller - Woolley, Jonathan N. (International Center for Tropical Agriculture, 1987)
The papers presented in the workshop on on-farm research on beans in Latin America held at CIAT and on farms in Narino (Colombia) from Feb. 16 to 25, 1987 are included. The various on- going activities on on-farm reasearch in different countries of Latin America are reported. These include Mexico, Ecuador, Colombia, Peru, Guatemala, Honduras, El Salvador, Paraguay, and Costa Rica. (CIAT)